Penerapan Pendekatan Contextual Teaching And Learning (CTL) Pada Materi Larutan Penyangga Kelas XI IPA 1 SMA Negeri 1 Poso Pesisir Utara - Riyadi, Bayu; Hamzah, Baharuddin; Sakung, Jamaluddin (Universitas Tadulako, 2015)
The use of learning approach applied to the study of chemistry is still one-way, the student just as a listener and not actively involved in the learning process. This research aims to determine the learning outcomes to the students who take buffer to the grade XI IPA I SMAN 1 Poso Pesisir Utara with contextual teaching and learning approach was better than the grade that follows the learning without contextual teaching and learning approach. The research population was all students of class XI IPA I SMAN 1 Poso Pesisir Utara in academic year 2013-2014 amounted to 65 studets were distributed in to classes. The research sample was determined by purposive sampling, 33 class XI IPA I as the experimental class and 32 class XI IPA 2 as control class. The data collection using test instruments in the form of 18 multiple-choice items that had been tested for validity and reliability. chemistry achievement of buffer test material, research data testing use t-test statistical p-analysis of the parties to the prerequisite test, test for normality and homogeneity tests. The analysis statistical hypothesis t-test was obtained value of tcalculate = 2.41 and ttable value = 1.67 this implies rejection of Ho. It can be concluded that the approach contextual teaching and learning effect on learning outcomes of students of the grade XI IPA I at SMAN 1 Poso Pesisir Utara in the material buffer with a good score than the conventional learning.